Pengaruh Serviks Care Terhadap Pemulihan Erosi Serviks pada Wanita Usia Subur di Wilayah Kerja Kecamatan Ngampel Kabupaten Kendal - Rahayu, M.Kep ., Sp.Kep.Mat, Ns. Tutik; Wahyuni, M.Kep., Sp.Kep.Mat, Ns. Sri (Jurnal Keperawatan Maternitas, 2015)
Cervical erosion is a process of inflammation or injury that occurred in the cervix . Causes of erosion can be due to infection , stimulation of certain chemicals or tools but is generally caused by infection . One effort that can be done to overcome cervical erosion is with cervical care . Research using pre experiment with one group pre and post test design with accidental sampling . The Analysis method by wilcoxcon test.